EVALUATION OF TRIBAL FOOD SECURITY IN NASHIK DISTRICTMAHARASHTRA (International Journal of Food and Nutritional Sciences, 2022)
- Food security, Food availability, food accessibility, food stability, food utilization,Juvenile Sex Ratio, working population